Nonsmooth Constraint Qualifications for Nonconvex Inequality Systems. (10th October 2022) - Bazargan, Fatemeh; Mohebi, Hossein
Abstract: In this paper, we study various nonsmooth constraint qualifications for a system of inequalities with tangentially convex functions. This is done by using the notion of tangential subdifferentials together with various nonsmooth (generalized) constraint qualifications that are a modification of the well known constraint qualifications. Indeed, we establish new links among various generalized constraint qualifications. We also give a table summarizing various links among the generalized constraint qualifications. Several illustrative examples are presented to clarify the connection between nonsmooth constraint qualifications.